Influence of Pre-Oxidation on High Temperature Oxidation and Corrosion Behavior of Ni-Based Aluminide Coating in Na2SO4 Salt at 1050°C - Li, Qing; Zhang, Defeng; Song, Peng; Li, Zhenhua; Zhai, Ruixiong; Hua, Chen; Lu, Jiansheng (Frontiers in Materials, 2021)
Aluminide coating is prepared on K438 Ni-base superalloy by pack cementation. The hot corrosion test of as-received and pre-oxidation aluminide coating in Na2SO4 salt is carried out at 1050 ℃. The coating morphologies, phase composition and corrosion products are characterized by XRD, SEM, EDS and TEM. The conclusion is that the pre-oxidation aluminide coating has excellent hot corrosion properties. After hot corrosion, the oxide scale of pre-oxidation aluminide coating is the thinnest and maintains good integrity. However, the oxide scale of as-received aluminide coating fluctuates greatly and there are corrosion cavities. CrS is formed in the alloy immediately below the oxide scale for the two coating systems.